2021
DOI: 10.3390/brainsci11070883
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Human TDP-43 Mislocalization Induces Widespread Dendritic Spine Loss in Mouse Upper Motor Neurons

Abstract: Amyotrophic lateral sclerosis (ALS) is defined by the destruction of upper- and lower motor neurons. Post-mortem, nearly all ALS cases are positive for cytoplasmic aggregates containing the DNA/RNA binding protein TDP-43. Recent studies indicate that this pathogenic mislocalization of TDP-43 may participate in generating hyperexcitability of the upper motor neurons, the earliest detectable change in ALS patients, yet the mechanisms driving this remain unclear. We investigated how mislocalisation of TDP-43 coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…Morphological analysis of the spines in these mice revealed a significant impairment in the development of mature spines in the motor cortex and lowered synaptic transmission (Handley et al, 2017). Consistent with these findings, mice expressing TDP-43∆NLS, a form of TDP-43 that is retained in the cytoplasm, in excitatory neurons under control of the Camk2α promoter, showed TDP-43∆NLS, and not TDP-43WT expression, caused a significant loss in spine density in layer V UMN, with few mature spines and mostly thin spines (Dyer et al, 2021a). These changes corresponded with a decreased expression in AMPA receptor subunits, Gria1, Gria2, and Gria3, and NMDA receptor subunit 2A and hyperexcitability in layer V excitatory neurons of the motor cortex (Dyer et al, 2021b).…”
Section: Tdp-43: Synaptic Dysfunction In Als/ftd Models Of Diseasesupporting
confidence: 68%
See 1 more Smart Citation
“…Morphological analysis of the spines in these mice revealed a significant impairment in the development of mature spines in the motor cortex and lowered synaptic transmission (Handley et al, 2017). Consistent with these findings, mice expressing TDP-43∆NLS, a form of TDP-43 that is retained in the cytoplasm, in excitatory neurons under control of the Camk2α promoter, showed TDP-43∆NLS, and not TDP-43WT expression, caused a significant loss in spine density in layer V UMN, with few mature spines and mostly thin spines (Dyer et al, 2021a). These changes corresponded with a decreased expression in AMPA receptor subunits, Gria1, Gria2, and Gria3, and NMDA receptor subunit 2A and hyperexcitability in layer V excitatory neurons of the motor cortex (Dyer et al, 2021b).…”
Section: Tdp-43: Synaptic Dysfunction In Als/ftd Models Of Diseasesupporting
confidence: 68%
“…Other reported changes in different TDP-43 mouse models involve alterations in dendritic branching and spines (Fogarty et al, 2016;Handley et al, 2017;Wu et al, 2019;Dyer et al, 2021a). Conditional knockout of TDP-43 in the mouse forebrain (TDP-43cKO) using the Camk2α promoter, showed that loss of TDP-43 in neurons caused dendritic attrition in layer V neurons UMN and loss of spines (Wu et al, 2019).…”
Section: Tdp-43: Synaptic Dysfunction In Als/ftd Models Of Diseasementioning
confidence: 99%
“…In the motor cortex, which is a principal site of ALS pathology, we observe a loss of plasticity in the form of decreased turnover and formation of dendritic spines. Whilst early changes to dendritic spine density have now been observed in a range of disease models and across cortical layers [41,53,54,92], our results are the first to show altered plasticity in areas of the mammalian brain which are dysfunctional in ALS, which is in agreement with the previous LTP and LTD studies [25,26,90,91]. ALS and FTD, which previously have been associated through genetic and pathological overlap, are now linked through a physiological mechanism-altered dendritic spine plasticity.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it appears that increased hyperexcitability can generate morphological changes. A study upon a nuclear localization sequence-deficient mouse model of TDP-43 identified that cytoplasmic mislocalization of TDP-43 drives intrinsic hyperexcitability and decreased excitatory synaptic inputs ( Dyer et al, 2021 ). Indeed, hyperexcitability may drive continued functional synaptic loss, dendritic spine loss and dendrite pathology in upper motor neurons that are commonly observed features in upper motor neurons of ALS patient post-mortem tissue ( Hammer et al, 1979 ; Genç et al, 2017 ) and other models, including TDP-43 A 315 T ( Handley et al, 2017 ), SOD1 G 93 A ( Fogarty et al, 2016b , 2017 ), and FUS R 521 G ( Sephtona et al, 2014 ).…”
Section: Cortical Dysfunction In C9orf72 Repeat Expansion-mediated Amyotrophic Lateral Sclerosis-frontotemporal Dementmentioning
confidence: 99%
“…Synaptic loss was observed in the prefrontal cortex of aged (4.5 months) transgenic mice expressing 80-repeat GR (GR 80 ) DPRs (Choi et al, 2019). TDP-43 mouse model shows intrinsic hyperexcitability and decreased excitatory synaptic inputs (Dyer et al, 2021).…”
Section: Post-symptomatic Cortical Neurophysiological Functionmentioning
confidence: 99%